Isolation and Characterization of Thermophilic Bacteria as Producing Enzyme Amylase from Kepanasan Hot Springs In Tapung Hulu, Kampar, Riau - Herwanda, Fadia Rezika; Linda, Tetty Marta (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Thermophilic bacteria are a group of bacteria that can live and survive at high temperatures ranging from 45°C-80°C. Thermophilic bacteria are the best choice as a producer of thermostable enzymes that can endure high temperatures used in various industrial fields including the textile industry, food industry, detergent industry, and pharmaceutical industry. This study aims to isolate, characterize, and test the activity of thermostable amylase enzyme from thermophilic bacterial isolates in Kepanasan hot spring in Tapung Hulu District, Kampar Regency, Riau. Characterization of thermophilic bacterial isolates is macroscopic, physiological, and biochemical tests: Triple sugar iron agar, Sulphur indole motility, symmons citrate, and catalase. The results of study obtained ten isolates of thermophilic bacteria consisting of six isolates from hot water samples and four isolates from soil sediments isolated at temperatures of 45°C and 50°C using a nutrient agar (NA) medium. The results of Gram staining were obtained one Gram-positive isolate and nine Gram-negative isolates. Positive catalase test results, negative indole and motility tests for ten isolates. The results of the amylase enzyme activity test obtained three bacterial isolates, namely BTA 6, BTT 2 and BTT 4 with the highest amylolytic index of 1.32 produced by BTT 2 isolate at an incubation temperature of 50°C with a starch concentration of 1%.